(untitled) (Teología, 2016)
The multifarious movements of migrations caused by wars, violence, poverty and the different infringements of human rights are signs of our time. Historically the word “peace” is associated with freedom and the space inhabitable of a city. What does it mean to talk about peace in a world in which cities, fee spaces and security are becoming more broken each time and even destroyed. Within this background this contribution attempts to design trails for a intercultural theology of peace and show some “spaces of peace” created by women.